2023
DOI: 10.3390/beverages9020047
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Rice, Tiger Nut and Carob for the Development of Fermented Beverages in Spain: A Comprehensive Review on the Production Methodologies Worldwide

Abstract: Rice, tiger nut and carob are Mediterranean products suitable for developing new foods, such as fermented beverages, due to their nutritional properties. These crops have a high carbohydrate content, are gluten and lactose-free and have a low allergenicity index. The development of fermented beverages from these crops can contribute to the Sustainable Development Goals by promoting human health and sustainable production and consumption. A narrative review of the nutritional value and potential functional acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 94 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…Its consumption was found to have numerous beneficial effects on human health, mainly due to its polyphenol and fiber content [ 2 , 3 ]. It was indeed suggested that the development of fermented beverages from this crop can contribute to the Sustainable Development Goals by promoting human health and sustainable production and consumption [ 8 ]. Moreover, the global plant-based beverage market has increased in the last decade, reaching a value of almost USD 20,000 million in 2023 [ 26 ], and several research papers have explored the possibility of using carob flour as an ingredient in new health-promoting beverages [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Its consumption was found to have numerous beneficial effects on human health, mainly due to its polyphenol and fiber content [ 2 , 3 ]. It was indeed suggested that the development of fermented beverages from this crop can contribute to the Sustainable Development Goals by promoting human health and sustainable production and consumption [ 8 ]. Moreover, the global plant-based beverage market has increased in the last decade, reaching a value of almost USD 20,000 million in 2023 [ 26 ], and several research papers have explored the possibility of using carob flour as an ingredient in new health-promoting beverages [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, fermentation with lactic acid bacteria is known, among other things, to increase the bioaccessibility of nutrients [ 27 ]. Reports on the use of fermentation to increase the bioavailability of carob nutrients while decreasing possible anti-nutritional factors can already be found [ 8 ]. The high presence of simple carbohydrates also makes carob an optimal substrate for fermentation by microorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations